A key to known species of Mastumyia Shiraki (Diptera, Syrphidae) from China, with descriptions of two new species - Huo, Keke K.; Ren, Guodong D. (Zootaxa, 2006)
Matsumyia zibaiensis sp. nov. and Matsumyia bimaculata sp. nov. are described from Mt. QinlingBasha, China, and a key to known species of Matsumyia Shiraki from China is compiled.